Refiguring the Romantic Body: Chinese Women Pianists in the American Conservatory - Vardanega, Audrey (Columbia Undergraduate Research Journal, 2017)
When the twenty-four-year-old pianist Yuja Wang walked on the stage of the Hollywood Bowl in a tight, short orange dress on August 2, 2011 to play the Third Rachmaninoff Piano Concerto under the direction of conductor Lionel Bringuier, Wang’s attire was interpreted as a transgression of normative expectations for classical performers. The Los Angeles Times reviewer Mark Swed described her dress as “so short and so tight that had there been any less of it, the Bowl might have been forced to restrict admission to any music lover under eighteen not accompanied by an adult…had her heels been any higher, walking, to say nothing of her sensitive pedaling, would have been unfeasible” (Swed 2011). The New Criterion reviewer Jay Nordlinger characterized it as “stripper-wear,” raising the question of how perceptions would change if the “pianist sitting before us were not a [tasteless] brash girl…but an antique, venerable Austro-German Meister” (Nordlinger 2011). Both critics’ comments highlight the significance of the body in classical music performances—where Wang’s clothing style or “stripper-wear” heightens the visibility of her body and draws attention to her sexiness, problematizing critics’ expectations for the comportment of the performing body (Ameer 2011).